2005
DOI: 10.1002/macp.200400465
|View full text |Cite
|
Sign up to set email alerts
|

Novel Phosphorous‐Containing Aromatic Polyethers – Synthesis and Characterization

Abstract: Summary: The synthesis of novel phosphorous‐containing aromatic polyethers P‐PEEK and P‐PSU, based on poly(ether ether ketone)s (PEEK) and poly(ether sulfone)s (PSU) was carried out successfully by using phosphorous‐containing aromatic diols instead of bisphenol A in the usual synthesis procedure. The molecular weights of the P‐PEEKs and P‐PSUs obtained reflect both the influence of the different halogen components used and the lower thermal stabilities of the phosphorous‐containing diols compared to bisphenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 13 publications
(27 reference statements)
1
34
0
Order By: Relevance
“…Phosphorus-modified polysulfones with side bulky groups were soluble in polar-aprotic solvents (N-methyl-2-pyrrolidone, dimethylacetamide, dimethylformamide), but also in some nonpolar solvents as chloroform and 1, 4 dioxane [48]. The solubility increases only in a certain extent with the substitution degree.…”
Section: Solubilitymentioning
confidence: 98%
See 2 more Smart Citations
“…Phosphorus-modified polysulfones with side bulky groups were soluble in polar-aprotic solvents (N-methyl-2-pyrrolidone, dimethylacetamide, dimethylformamide), but also in some nonpolar solvents as chloroform and 1, 4 dioxane [48]. The solubility increases only in a certain extent with the substitution degree.…”
Section: Solubilitymentioning
confidence: 98%
“…Recently, it was proposed to incorporate phosphorus-containing diols into the polymer to further improve the fire behaviour of poly(ether sulfone) [48] and hence to use these new materials not only as toughness modifier for epoxy resins, but also as flame retardant at the same time. It should be noted that fire retardants containing phosphorus -regardless of whether an additive or reactive approach is used, show different mechanisms in the condensed and gas phase [115].…”
Section: Flame Resistant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that incorporating asymmetric pendants [17][18][19][20][21][22][23][24][25][26][27][28][29][30] into polymers can enhance the T g of polymers due to restricted segmental mobility. As a result, preparation of bisphenol monomers with bulky pendant for poly(ether sulfone)s may be a route for high-T g poly(ether sulfone)s. Herein, three poly(ether sulfone)s…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] The utilization of monomers that contain phosphorus units, such as 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), which possesses a polar P¼O group and a bulky structure, resulted in polymers with good solubility and decreased birefringence. [17][18][19][20][21][22][23] Previously, thermotropic polyesters and copolyesters were prepared by the polycondensation reaction of a diacid chloride, namely terephthaloyl-bis(4-oxybenzoyl-chloride), with 2-(6-oxido-6H-dibenzhc,eih1,2ioxaphosphorin-6-yl)-1,4-benzenediol, or with an equimolar amount of the latter and an aromatic or aliphatic diol. [24,25] The polymers had a good thermal stability and some of them exhibited a thermotropic behavior.…”
Section: Introductionmentioning
confidence: 99%